The Monotonicity And Sub-Additivity Properties Of Fuzzy Inference Systems And Their Applications - Tay , Kai Meng (2011)

(untitled)
The Fuzzy Inference System (FIS) is a popular computing paradigm for undertaking modelling, control, and decision-making problems. In this thesis, the focus of investigation is on two theoretical properties of an FIS model, i.e., the monotonicity and sub-additivity properties. These properties are defined, and their applicability to tackling real-world problems is discussed. This research contributes to formulating a systematic procedure that is based on a mathematical foundation (i.e., the sufficient conditions) to develop monotonicity-preserving FIS models. A method to improve the sub-additivity property is also proposed.